2007
DOI: 10.2353/ajpath.2007.061002
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Abnormalities in Heterozygous Acid Sphingomyelinase Knockout Mice Reveal a Novel Approach for the Prevention of Genetic Diseases

Abstract: Acid sphingomyelinase knockout mice are a model of the inherited human disorder types A and B NiemannPick disease. Herein, we show that heterozygous (ASMKO ؉/؊ ) mice have two distinct sperm populations resembling those found in normal and mutant animals, respectively, and that these two populations could be distinguished by their morphology, ability to undergo capacitation or the acrosome reaction, and/or mitochondrial membrane potential (MMP). The abnormal morphology of the mutant sperm could be normalized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Through regulated secretion and reabsorption, they control the pH, osmotic pressure, and composition of epididymal fluids and also the transfer of metabolites such as proteins, sugars, and lipids to and from the sperm surface. Interactions with the proximal epididymis are essential for the acquisition of fertilizing ability by sperm, and alteration of the genes encoding several proteins secreted from the epididymal epithelium often leads to male infertility as a result of defective sperm motility or morphology (10,42,(56)(57)(58)(59). We found that sPLA 2 -III is expressed in the proximal epididymal epithelium and secreted into the luminal fluid (Figures 1 and 2), that spermatozoa of Pla2g3 -/-mice are numerically normal but functionally and structurally abnormal (Figures 3-5), and that epididymal sperm of Pla2g3 -/-mice have an altered phospholipid composition ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Through regulated secretion and reabsorption, they control the pH, osmotic pressure, and composition of epididymal fluids and also the transfer of metabolites such as proteins, sugars, and lipids to and from the sperm surface. Interactions with the proximal epididymis are essential for the acquisition of fertilizing ability by sperm, and alteration of the genes encoding several proteins secreted from the epididymal epithelium often leads to male infertility as a result of defective sperm motility or morphology (10,42,(56)(57)(58)(59). We found that sPLA 2 -III is expressed in the proximal epididymal epithelium and secreted into the luminal fluid (Figures 1 and 2), that spermatozoa of Pla2g3 -/-mice are numerically normal but functionally and structurally abnormal (Figures 3-5), and that epididymal sperm of Pla2g3 -/-mice have an altered phospholipid composition ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Although they produced normal numbers of sperm, heterozygotes demonstrated abnormal sperm morphology, mitochondrial membrane potential and ability to undergo capacitation or the acrosome reaction. Strikingly, when sperm from heterozygous ASMKO mice was used for in vitro fertilization of heterozygous oocytes followed by implantation into pseudopregnant wild-type mice, 37.8% of the resulting offspring were normal and 15.6% of the offspring were ASMKO affected mice [47]. Also, mice heterozygous for the βgal knockout mutation produced offspring of which 18% were affected by G M1 gangliosidosis [44], and sperm abnormalities have been reported in the mouse models of Niemann-Pick Disease type C [48] and globoid cell leukodystrophy (Twitcher mouse) [49].…”
Section: Discussionmentioning
confidence: 99%
“…The generation of such Cer from SM as precursor requires either (i) a form of SMase that is specifi c for 2-OH VLCPUFA-containing species of SM, or (ii) an ordinary SMase that expresses itself in a cell-specifi c manner in spermatids. Mice defi cient in acid SMase in their lysosomes (a model of the human Niemann-Pick disease), accumulate SM in their tissues, including testis (mostly as lipid inclusions in Sertoli cells), and produce spermatozoa that develop an abnormal motility (40)(41)(42). The latter of these defects correlated with an excess of surface area in the midpiece of the sperm tail in late spermatids and spermatozoa, with the mature gametes showing a rigid bending of their tails that preclude normal motility.…”
Section: Germ Cell-neutral Lipidsmentioning
confidence: 99%